Subsistence patterns of population of the Lower Ob river basin during the Eneolithic (based on faunal remains of the settlement of Gorniy Samotnel-1) - Nomokonova T.Yu.; Losey R. J.; Tupakhina O.S.; Tupakhin D.S. (VESTNIK ARHEOLOGII, ANTROPOLOGII I ETNOGRAFII, 2017)
This article is dedicated to the analysis of faunal remains found at the Eneolithic settlement of Gorniy Samotnel-1. This habitation site has a modeled age spanning from 3060 to 2920 cal. BC, firmly within the Middle Holocene. This site is located on the territory of Yamalo-Nenets Autonomous Region on the shore of the Ob’ river. The paper considers the identification of faunal remains from the site, their relative abundances, bone modification (such as natural erosion, carnivore gnawing, butchering traces, and tool making), as well as proportions of skeletal elements and reconstruction of age at death of some individuals. The resulting data demonstrate relatively broad use of natural resources by the inhabitants of Gorniy Samotnel-1 during the Eneolithic, despite a relatively small size of the analyzed assemblage. The results of species identification and other faunal analyses are discussed in association with the rest of the archaeological context. In addition, the article includes information on the reconstruction of paleodiet based on the stable isotope analyses of the residues of pottery vessels at the site. Finally we introduce the zoomorphic images at the site, including possible depictions of elk and waterfowl, which were found in a direct association with the site’s faunal remains.